Nicotinamide Adenine Dinucleotide (NAD+) and Enkephalinase Inhibition (IV1114589NAD) Infusions Significantly Attenuate Psychiatric Burden Sequalae in Substance Use Disorder (SUD) in Fifty Cases - Blum, Kenneth; Han, David; Baron, David; Kazmi, Shan; Elman, Igor; Gomez, Luis L.; Gondre -Lewis, Marjorie C.; Thanos, Panyotis K; Braverman, Eric R; Badgaiyan, Rajendra D (Current Psychiatry Research and Reviews, 2022)
Background: There is a shortage of clinical studies examining the efficacy of Nicotinamide Adenine Dinucleotide and Enkephalinase infusions (IV1114589NAD) in treating Substance Use Disorder (SUD). Objective: This study aims to provide evidence that IV1114589NAD infusions significantly attenuate substance craving behavior. Methods: The study cohort consisted of addicted poly-drug, mixed gender, multi-ethnic individuals resistant to standard treatment. The investigation utilized Likert-Scales to assess behavioral outcomes. Results: Using Wilcoxon signed-rank tests and sign tests, our team detected significant results by comparing baseline to post outcome scores after IV1114589NAD injections: craving scores (P=1.063E-9); anxiety (P=5.487E-7); and depression (P=1.763E-4). A significant reduction in cravings, anxiety, and depression followed a dose-dependent linear trend. Linear trend analyses showed a significant relationship between NAD infusions and decreasing scores for cravings (P=0.015), anxiety (P=0.003), and depression (P=8.74E- 5). A urine analysis was conducted on a subset of 40 patients midway through the study to assess relapse; 100% of the urine samples analyzed failed to detect illicit substance use. Discussion: The opioid crisis in America has claimed close to 800,000 lives since 2004; daily deaths are estimated to stand at 127, and in 2021, over 107,000 deaths were due to overdose. There is an urgency to find safe, side-effect-free solutions. Current interventions, such as Naltrexone implants, are invasive and may interfere with dopamine homeostasis leading to an anti-reward phenomenon. Larger randomized double-blinded placebo-controlled studies are needed to elucidate further the significance of the results presented in this study. The current pilot study provides useful preliminary data regarding the effectiveness of IV1114589NAD infusions in SUD treatment. Conclusion: This pilot study provides significant evidence that NAD infusions are beneficial in the treatment of SUD. This investigation serves as a rationale to extend these findings onto future research investigating the use of NAD/NADH as a stand-alone treatment, especially in patients showing high genetic risk as measured in the Genetic Addiction Risk Severity (GARS) test. Utilizing GARS will help provide a real personalized therapeutic approach to treat Reward Deficiency Syndrome (RDS).
Keywords: Nicotinamide adenine dinucleotide (ND+) infusions